Penentuan Indeks Pencemaran Air dan Daya Tampung Beban Pencemaran Menggunakan Software QUAL2Kw (Studi Kasus Sungai Brantas Kota Malang) - Novia Lusiana; Akhmad Adi Sulianto; Luhur Akbar Devianto; Septyana Sabina (Department of Urban and Regional Planning, Diponegoro University, 2020)
Starting in 2000, the growth of population and industries sector rapidly increased in Brantas Hulu’s river. This phenomenon brought environmental issues since most of industries dispose of their waste including organic-based pollution to the surrounding river. It contaminates the river and lowers the water quality. Minimum assessment on water contamination in Brantas River attracts the research on the area. The study aims to assess water quality on Brantas River based on several parameters: water quality pattern using QUAL2Kw model, determine of pollution level using pollutant index and pollution load capacity. The research relied on a quantitative description by measuring pollution level and calculating acceptable pollution load. The result shows that 10 from 12 sampling areas produced low pollution levels, while the others are moderate level of pollution. The most pollutant found in the Brantas River were BOD, nitrate, ammonia and phosphate. Simulation results from QUAL2Kw model accounted for 10.7% of error rate.